Effects of pulsed dye laser on the procollagen mRNA expression and proliferation of cultured fibroblasts in vitro - YU Hai-yan; FANG Qing; CHEN Da-fang; CHENG Hao (浙江大学学报. 农业与生命科学版, 2005)
Cultured fibroblasts were exposed to 585-nm flashlamp-pumped pulsed dye laser (fluence 3 J/cm2, 5 J/cm2,7 J/cm2, spot size 7 mm, pulse duration 450 μs) followed by 24 h incubation. The proliferation of fibroblasts was measured by MTT methods and the expression of the procollagen mRNA and SMADs was investigated by real time PCR method. The results showed that 585 nm flashlamp-pumped pulsed dye laser inhibited the proliferation of fibroblasts after exposure to fluence of 5 J/cm2 and 7 J/cm2 (P<0.05). The mRNA expression of procollagen Ⅰα1 and SMAD2, 3, 4, 7 was significantly down-regulated after being treated with 585 nm flashlamp-pumped pulsed dye laser at fluence level of 5 J/cm2 (P<0.01, or P<0.05). The corresponding fluence level for significant down-regulation of mRNA expression of procollage Ⅲ α1 was 6 J/cm2 and 7 J/cm2 (P<0.05). It is concluded that sufficiently high level fluence of 585 nm flashlamp-pumped pulsed dye laser may inhibit the proliferation of fibroblasts in dose-dependent manner in vitro and down- regulate procollagen mRNA expression.